Experimental and numerical analysis of particulate matter deposition in DPF for different blends of Algae Bio diesel - Nalawade, Jayant; Ramakrishnan, Prakash (Edelweiss Applied Science and Technology, 2024)
The stringent emission norms have compelled to use Diesel particulate filter (DPF) to reduce particulates emission in automotive Diesel engine. The back pressure developed in the DPF due to the Particulates matter (PM) deposition in porous zone degrades the diesel engine’s performance. So, there is a need of a fuel which should produce less particulates on combustion as well as its produced particulates should be easy to get regenerated inside the DPF. Three different Algae biodiesel blends B20, B40 and B60 were selected for the study, while the results are compared with the diesel fuel. A numerical study has been done with diesel and Algae biodiesel blends to investigate the effect of PM deposition on the DPF performance. The results of PM concentration and the pressure drop has been predicted for t = 2000s. and compared with the results predicted for diesel fuel. The summarized velocity contours and the PM concentration plots show that a maximum of the PM concentration was found in the diesel fuel case, while the lower found in B60 algae blend. Also, the pressure drop was found to increase with the increase in PM deposition in each case of fuel. The SEM-EDS analysis is done after collecting PM samples after combustion shows a higher percentage of Oxygen and lower Carbon with an increment of Biodiesel in the blend. This work provides a brief idea about the PM deposition in DPF while using Diesel and Algae Biodiesel blends and highlighting the better fuel option for Diesel Engine.